2014
DOI: 10.5070/v426110476
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Fertility Management Bait Uptake by Urban Rats within New York City Subway Refuse Rooms

Abstract: Traditional rodent management tools, such as traps and lethal rodenticides, are acute measures to reduce commensal rodent populations. Given the growing concerns regarding effectiveness, environmental safety, and animal welfare related to these tools, it has become imperative to find new methods. Fertility control is an emerging potential alternative to these tools as a safe, humane and effective method of long-term population management. SenesTech, Inc. has developed a liquid fertility management bait that ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…A palatability trial was conducted in subway refuse rooms in New York City. This trial confirmed that urban wild Norway rats would consume ContraPest ® while in the presence of abundant alternative food sources (Pyzyna et al 2014). Following this trial, two additional trials utilizing ContraPest ® in complex urban environments have been conducted in mid-western US and northeastern US.…”
Section: Urban Trialssupporting
confidence: 56%
“…A palatability trial was conducted in subway refuse rooms in New York City. This trial confirmed that urban wild Norway rats would consume ContraPest ® while in the presence of abundant alternative food sources (Pyzyna et al 2014). Following this trial, two additional trials utilizing ContraPest ® in complex urban environments have been conducted in mid-western US and northeastern US.…”
Section: Urban Trialssupporting
confidence: 56%
“…For example, combinations of 4-vinylcyclohexene diepoxide and triptolide have been shown to be highly effective in modifying Rattus life history traits. In females, litter number is reduced by increasing the overall concentration in each dose; litter size is reduced by varying dosage frequency; in males, even greater sensitivity to dosage exists and may lead to lifelong sterility in some individuals (Mayer et al., 2002, 2004; Dyer et al., 2013; Dyer and Mayer, 2014; Pyzyna et al., 2014). Note that while chemically induced sterility can often be induced in both sexes, this is usually not the means by which males are sterilized in the sterile-male treatments of pest populations described above (Knipling, 1959; Knipling and McGuire, 1972; Krasfur, 1998; Klassen and Curtis, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Despite aggressive campaigns to cull rat populations, R. norvegicus numbers are estimated to exceed 175 million in the US alone, and attempts at population control cost in excess of $20 billion each year (Pimentel et al., 2005). Additional consequences and costs of Rattus populations' explosive rates of increase, as well as current methods for rodent control are reviewed in detail elsewhere (Seamark, 2001; Singleton, 2003; Jacob et al., 2006, 2008; Pyzyna et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ContraPest ® has been shown to be palatable to free living wild rats (Pyzyna et al 2014) and decreased offspring numbers in both laboratory and wild rats in captivity (Witmer et al 2017). An open arena breeding study was conducted at the USDA National Wildlife Research Center (NWRC) in Fort Collins, CO.…”
Section: Introductionmentioning
confidence: 99%